Pengawasan Partisipatif Dalam Mencegah Pelanggaran Pemilu 2024: Studi di Bawaslu Kota Blitar - Erwin Widhiandono; Rosa Widya Ningtyas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Indonesia, as a rule of law country, establishes the conduct of General Elections (Pemilu) based on Article 22E paragraph (1) of the 1945 Constitution of the Republic of Indonesia: